Array - Wijayanti, Riva; Sukardani, Puspita Sari (The Commercium, 2022)
This study aims to determine the effect of storytelling content on purchasing decisions for local product perfume "HMNS". Researchers researched about HMNS in marketing its brand through Instagram with the Storytelling marketing strategy. The population of this study is Instagram followers @hmns.id. The sample of respondents as many as 400 people with sampling using purposive sampling and determining the sample using the Slovin formula. With a simple linear regression descriptive analysis through the SPSS 25 program. This research uses the AIDDA (Attention, Interest, Desire, Decision, and Action) model. As the theoretical model, this is the stage of consumers in getting to know the product until they decide to consume the product they choose. With the Positivism paradigm and a quantitative approach using a survey method that is distributed to Instagram followers @hmns.id, especially users of the "HMNS" product. Data collection techniques with indirect field surveys and questionnaires. The results obtained in this study indicate that storytelling content has a significant positive influence on purchasing decisions but has low value. Keywords: Storytelling content, marketing, purchasing decisions